2006
DOI: 10.1254/jphs.fp0050863
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Endothelium-Independent Relaxation Induced by the Wine Polyphenol Resveratrol in Human Internal Mammary Artery

Abstract: Abstract. Resveratrol, a stilbene polyphenol found in grapes and red wine, produces vasorelaxation in both endothelium-dependent and endothelium-independent manners. The mechanisms by which resveratrol causes vasodilatation are uncertain. The aim of this study was to investigate the mechanism(s) of endothelium-independent resveratrol-induced vasorelaxation in human internal mammary artery (HIMA) obtained from male patients undergoing coronary artery bypass surgery and to clarify the contribution of different K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 26 publications
6
78
0
Order By: Relevance
“…By showing that, like glibenclamide, resveratrol can act as a blocker of the SUR1/K IR 6.2 channel, we have provided further evidence for analogies between both substances. In previous studies, a stimulatory effect of resveratrol on Ca 2ϩ -activated or voltage-gated K ϩ channels was reported, but no evidence for an effect on K ATP channels was obtained (45)(46)(47). Because the subunit composition of K ATP channels might be decisive in this respect, a systematic comparison of channels containing different SUR isoforms could be of future interest.…”
Section: Discussionmentioning
confidence: 99%
“…By showing that, like glibenclamide, resveratrol can act as a blocker of the SUR1/K IR 6.2 channel, we have provided further evidence for analogies between both substances. In previous studies, a stimulatory effect of resveratrol on Ca 2ϩ -activated or voltage-gated K ϩ channels was reported, but no evidence for an effect on K ATP channels was obtained (45)(46)(47). Because the subunit composition of K ATP channels might be decisive in this respect, a systematic comparison of channels containing different SUR isoforms could be of future interest.…”
Section: Discussionmentioning
confidence: 99%
“…116 The same group repeated the study using endothelium-independent human internal mammary artery (HIMA) obtained from male patients undergoing coronary artery bypass surgery, and a similar conclusion was reached. 117 Resveratrol also inhibits the production of endogenous vasoconstrictors. In vascular smooth muscle cells (VSMCs) generation of oxidative stress induced endothelin-1 (ET-1) was inhibited by resveratrol.…”
Section: Effect On Vasorelaxationmentioning
confidence: 99%
“…Also, in different experimental models, resveratrol can activate adenylate cyclase and membrane-bound guanylyl cyclase and inhibit cGMP-specific phosphodiesterse-5 (13 -15). Previously, we have shown that resveratrol produces relaxation of the isolated human internal mammary artery and rat aorta by activation of margatoxin-sensitive voltage-dependent K + (K V ) channels located in the smooth muscle (7,16). In contrast, Orsini et al (17) suggested that resveratrol derivates inhibited K V channels in the F-11 neuroblastoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…The resveratrol-induced vasorelaxation may either be endothelium-dependent (attenuated by L-NAME) or endothelium-independent (6,7,10). The mechanism of endothelium-independent vasorelaxation induced by resveratrol is uncertain.…”
Section: Introductionmentioning
confidence: 99%